Outcomes of Chronic Hepatitis C Treatment in The Infectious Diseases Hospital Iasi - Mihaela Catalina Luca; A. Vata; A. Luca; Carmen Dorobat (Romanian Society of Oral Rehabilitation, 2012)
Chronic hepatitis C is an important cause of morbidity and mortality due o hepatic disease. Material and method The retrospectively studied the evolution of 30 patients with chronic hepatitis C, treated in the Infectious Diseases Hospital of Iasi, with Peginterferon and Ribavirin for 48 weeks. Results 18 patients were treated with Peginterferon α2a and Ribavirin, and 12 with Peginterferon α2b and Ribavirin. Most of them (73.3%) were adults, aged between 30 and 50 years, with a sex ratio M/F - 13/17. Most of them had risk factors for the transmission of HCV: 28 of them suffered surgery and 2 of them had infected sexual partners. 3 patients didn't achieve a rapid virusologic response and 6 patients were relapsers. All the other 70% of patients had a sustained virologic response. The side effects were present in all patients, with a moderate intensity. Conclusion The success (SVR) rate of antiviral therapy was higher than expected (especially for genotype 1 HCV). The patients with a viral relapse could be soon treated with the new protease inhibitors and hope for a cure.